Психология художественного творчества: учебное пособие для вузов / Л. Б. Ермолаева-Томина - Ермолаева-Томина Людмила Борисовна (Gaudeamus, 2005)
Экземпляры: СЭ (20130129) / Инвентарный номер: 1090059 / Цена: / Сис.шифр: 88.4 / Авт.знак: Е 74 / ГРНТИ: 15 / ББК: 88.45